Peter Paul Rubens, Nicolas-Claude Fabri de Peiresc and Joan of Arc - Borusowski, Piotr (Werkwinkel, 2015)
In 2011 a discovery was made at the Department of Prints and Drawings of the National Museum in Warsaw – a drawing hitherto described as a Kneeling knight by an anonymous seventeenth-century artist, turned out to be Joan of Arc, a sketch well-known to art historians studying the oeuvre of Peter Paul Rubens, although thought to be lost during the Second World War. The drawing, until now known only through the black and white photograph, could be thoroughly analysed for the first time. In the context of information thus obtained, the historical context of creating the sketch transpired as an equally important matter, including the hypothetical role that may have been played in its creation by Nicolas-Claude Fabri de Peiresc.